The definitive management ideas of the year from Harvard Business Review (Boston, 2019)
This book will inspire you to: Make stronger connections and build greater trust among people who work on multiple teams. Engage customers and employees alike with the help of artificial intelligence. Channel your outrage about sexual harassment in the workplace into effective action. Consider how CEO activism can generate goodwill for your company--and weigh its risks. Pair data with qualitative research to increase diversity in your organization. Remain competitive in a hub economy by using your company's assets and capabilities differently.
Keywords: Quản trị học,Management